Bio-equivalence Study of Two Oral Flumequine Formulations (FlumisolÂ® and MaquinÂ®) in Broiler Chickens - El-Hanbally, Saber (Journal of Medical Biomedical and Applied Sciences, 2016)
The present study was designed to assess the comparative bio-equivalence of FlumisolÂ®and MaquinÂ® in healthybroiler chickens after oral administration of both products in a dose of 12 mg flumequine /kg.b.wt. Twenty four broilerchickens were divided equally into two groups (12 chickens for each group). The first group was designed to study thepharmacokinetics of FlumisolÂ®, while the 2nd group was designed to study the pharmacokinetics of MaquinÂ®. Eachbroiler chicken in both groups was orally administered with 12 mg flumequine /kg b.wt. Blood samples were obtainedfrom the wing vein and collected immediately before and at 0.08, 0.16, 0.25, 0.5, 1, 2, 4, 6, 8, 12 and 24 hours aftera single oral administration. The disposition kinetics of FlumisolÂ® and MaquinÂ® following oral administration of 12 mgflumequine/kg b.wt, revealed that the maximum blood concentration [Cmax] were 1.88 and 1.76 g/ml, attained at [tmax]of 1.42 and 1.41 hours, respectively.In conclusion: MaquinÂ® is bioequivalent to FlumisolÂ® since the ratios of Cmax, AUC0ô24 and AUC0ô1 (T/R) were0.93, 0.89 and 0.88, respectively. These are within the Bio-equivalence acceptance range. FlumisolÂ® and MaquinÂ®are therefore bioequivalent and interchangeable.